The developmental origins of health and disease in international perspective. (September 2018) - Haas, Steven A.; Oi, Katsuya
Abstract: The developmental origins of health and disease and the comparative international approach are two important strands of research exploring population health. Despite the potential insights to be gained from integrating the two approaches, their nexus remains an underexplored frontier. The current study investigates international variation in the early life origins of health among aging cohorts in 13 countries. We examine cross-national differences in exposure to poor childhood health and socioeconomic disadvantage, whether the long-term health associations with those exposures vary across contexts, and whether they persist in the face of subsequent accumulation of socioeconomic and behavioral risk. Finally, we investigate whether childhood health and socioeconomic circumstances help explain between-country differences in later life health. The findings suggest substantial international variation in the exposure to early life health and socioeconomic insults. We also find variation in their association with later life health. However, early life factors appear to play a modest role in explaining international differences in later life health in the contexts examined here. Highlights: We study international variation in life course influences on health. Early life health & socioeconomic exposures vary across countries. The long-term impacts of early life exposures also vary across countries. Life course processes explain a modest portion of variation in adult health in Europe.